(3caGjI GdeMJGL aj eYQaI GdENJdGLs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3GScfOQ GdjhfGfj GdMcjes ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe s)
(3ChdgG (B:s
(3GdMeO ddg hcai hSdGe Ydi YHGOg GddPjf EUWai hHYO agPg QSGdI dWjaI ai ENJdGL GdCYVGA hVYgG Ph GdbQfjf CScfOQ GdjhfGfi GdMcje Ydjg GdSdGe s
(3BNQgG (B:s
(3hEPG cGf GUGHY GdQLd GdjSQi CUGH ELdGdkG hJYXjekG hGddg JYGdi CYde HGdUhGHI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B24s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg aGFOgHgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3gi deDdagG EScfOQ GdjhfGfi GdMjce s
(3hQO ai cTa GdXfhf ai L(B1 (3U` (B32 (3Cf QSGdI ENJdGL GdCYVGA s
(3bQf GdfSN (B:s
Keywords: (3GdeLGejYs